Sound linkage : an integrated programme for overcoming reading difficulties - Hatcher, P. J. (Peter J.); Duff, Fiona J.; Hulme, Charles (Chichester, West Sussex, UK : Wiley Blackwell, 2014)
'The updated edition of this successful resource has been developed to support children with reading delays and dyslexia. It contains a phonological training programme, an explanation of how this programme can be embedded within a broader reading intervention, a standardized test of phonological awareness and a methodology to grade children's reading books. This third edition has been revised throughout to include the latest developments in the field These resources have been used with a wide range of children and found to be suitable for use with any reading-delayed children, irrespective of cognitive ability and age All activities are accompanied by a set of photocopiable record sheets, a set of pictures, and an appendix of additional activities useful in helping children master a particular skill or to reinforce existing learning The ten sections of activities within the guide include: identification of words and syllables; identification and supply of rhyming words; identification and discrimination of phonemes; and blending, segmentation, deletion, substitution and transposition of phonemes within words.'--
Includes bibliographical references.
Keywords: Reading -- Phonetic method; Reading -- Remedial teaching; Phonetics -- Study and teaching (Elementary).; Learning disabled children -- Education (Elementary).